2022
DOI: 10.1055/s-0042-1744307
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Cardiorespiratory Physiotherapy during Mechanical Ventilation

Abstract: Physiotherapists are integral members of the multidisciplinary team managing critically ill adult patients. However, the scope and role of physiotherapists vary widely internationally, with physiotherapists in some countries moving away from providing early and proactive respiratory care in the intensive care unit (ICU) and focusing more on early mobilization and rehabilitation. This article provides an update of cardiorespiratory physiotherapy for patients receiving mechanical ventilation in ICU. Common and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…The choice of treatment was based on the patient's respiratory dysfunction in order to obtain effects of volume, flow or airway clearance. According to a recent study (Tronstad et al., 2022), the choice of treatment should be selected based on the underlying problem and the best way(s) of addressing this. Tronstad has also described a pathway and treatment modalities for physiotherapy treatments to address key respiratory problems responsive to respiratory physiotherapy in ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of treatment was based on the patient's respiratory dysfunction in order to obtain effects of volume, flow or airway clearance. According to a recent study (Tronstad et al., 2022), the choice of treatment should be selected based on the underlying problem and the best way(s) of addressing this. Tronstad has also described a pathway and treatment modalities for physiotherapy treatments to address key respiratory problems responsive to respiratory physiotherapy in ICU.…”
Section: Discussionmentioning
confidence: 99%
“…18-20,23 Emerging novel assessments including lung ultrasound 33 were only used sometimes by 16.5% of physical therapists which is of concern as the outcome measures more commonly used by physical therapists such as lung auscultation and the chest radiograph findings have poor diagnostic accuracy when compared to lung ultrasound. 33 The use of lung ultrasound is expected to further develop considering the evolving evidence base 1,34 supporting its use in ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapy is considered a standard of care in many intensive care units (ICUs). 1 The goals of cardiopulmonary physical therapy management are to promote secretion clearance, maintain or recruit lung volume, optimize oxygenation, prevent respiratory complications, and initiate early rehabilitation to prevent deconditioning and decline in functional mobility in both the intubated and spontaneously breathing patient. 2 A systematic review by Stiller 3 concluded that the provision of routine cardiopulmonary physical therapy has been questioned with conflicting evidence from randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of time to extubation may be more appropriate since it is associated with both ICU- and post-discharge morbidity and mortality in critically ill adults, representing a patient-centered outcome measure ( 37 ). Other outcome measures might include re-intubation rate, which is potentially associated with acquisition of ventilatory acquired pneumonia ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…If necessary, modification of MV settings during mobilization/exercise were adopted according to the respiratory need of the patient. Moreover, airway clearance strategies were proposed as well as lung expansion techniques (i.e., deep breathing exercises) ( 22 ). When patients were completely awake and started weaning from MV, physiotherapists assessed their ability to perform bed mobility activities and to reach and maintain sitting and vertical position while receiving minimal or no ventilator support.…”
Section: Methodsmentioning
confidence: 99%